Rethinking the Principle of Obedience to Eradicate Terrorist Women in Indonesia - Alponso Munte; Desi Natalia (TEMALI : Jurnal Pembangunan Sosial, 2022)
In society, there are symptoms of women as suicide bombers. This act of terror robs Human Rights. Here, acts of terror seem to be something banal. This paper aims to dissect what philosophy can relieve the symptoms of female terrorists. This study is a discourse analysis with a philosophical review of Hannah Arendt regarding the banality of crime and obedience. This paper finds that people at the grassroots level in Indonesia still think that the concept of obedience by putting aside critical thinking is a virtue and can also be a threat to humanity universally. From the existing discourse, the writer finds that the answer to this problem is awareness of citizenship compliance. This study contributes to the re-emergence of philosophy in social studies. The root of sociology itself is a philosophy that always invites back rationality in every decision and action.